Detailed characterisation of circulatory nitric oxide and free radical indices—is there evidence for abnormal cardiovascular homeostasis in young women with polycystic ovary syndrome?. (12th May 2014) - Willis, GR; Udiawar, M; Evans, WD; Blundell, HL; James, PE; Rees, DA
<x xml:space="preserve">Abstract</x> Objective To assess circulating biochemical indices of endothelial function and nitro‐oxidative stress in women with polycystic ovary syndrome (PCOS). Design Case–control study. Population Seventeen women with PCOS and eighteen age‐ and body mass index‐matched healthy volunteers. Methods Nitric oxide (NO) metabolite levels were assessed by chemiluminescence. Electron paramagnetic resonance spectroscopy with spin trapping was used to assess oxidative stress ex vivo and in vitro. Antioxidant capacity was measured using oxygen radical absorbance. Main outcome measures Biochemical indices of endothelial function, including NO metabolites, lipid‐derived radicals and antioxidant capacity. Results Plasma NO metabolites were similar in the two groups (nitrite: 257 ± 116 nmol/l [PCOS], 261 ± 135 nmol/l [controls] P = 0.93; nitrate: 27 ± 7 μmol/l [PCOS], 26 ± 6 μmol/l [controls] P = 0.89). Alkoxyl free radicals (lipid‐derived) were detected as the dominant species, but levels were not different between women with PCOS and controls whether measured directly ex vivo (median 7.2 [range 0.17–16.73]e6 arbitrary units [a.u.] and 7.2 [1.7–11.9]e6 a.u., respectively, P = 0.57) or when stimulated in vitro to test radical generation capacity (1.23 [0.3–5.62]e7 a.u. and 1.1 [0.48–15.7]e7 a.u. respectively, P = 0.71). In regression analysis, visceral fat area was independently associated with in vitro oxidative potential (β = 0.6, P = 0.002). Total plasma antioxidant capacity (94 ± 30% [PCOS], 79 ± 24% [controls], P = 0.09) and plasma hydroperoxides (7.5 ± 4 μmol/l [PCOS], 6.7 ± 5 μmol/l [controls], P = 0.21) were not different between groups. However, lipophilic antioxidant capacity was lower in women with PCOS compared with controls (92 ± 32 and 125 ± 48%, respectively, P = 0.02). Conclusions Young overweight women with PCOS display a reduced lipophilic antioxidant capacity compared with healthy volunteers, but no change in circulating free radicals or nitro‐oxidative stress.